Early Portuguese data for wage developments in India : Kannur (Cananor), 1516-1517 - Matos, P. T. De; Lucassen, J. (Ler História, 2019)
This essay discusses new evidence for wage developments in Western India from c. 1300 to 1600. By introducing wage and price data for Kannur (Cananor in Portuguese and British sources) for the years 1516-1517 we contribute to a larger discussion about standards of living in South Asia. These figures from unpublished Portuguese archival sources are compared to Indian ones for the early fourteenth and late sixteenth centuries (no other being available so far). We conclude that the overall purchasing power of wage earners in Kannur in 1516-1517 was not substantially lower than in Delhi 1311. This suggests that real wages remained stable at a low level in the fourteenth and fifteenth centuries, then rose during the sixteenth century to an all-time high around 1600, before dropping again (if expressed in grain), though never returning to the low levels of 1300-1500.